Goodbye cinema, hello cinephilia : film culture in transition - Rosenbaum, Jonathan (Chicago ; London : The University of Chicago Press, 2010)
Goodbye cinema, hello cinephilia -- In defense of spoilers -- Potential perils of the director's cut -- Southern movies, actual and fanciful: a personal survey -- À la recherche de Luc Moullet: 25 propositions -- Bushwhacked cinema -- What dope does to movies -- Fever dreams in Bologna -- From playtime to the world: the expansion and depletion of space within global economies -- Kim Novak as midwestern independent -- Marilyn Monroe's brains -- A free man: white hunter, black heart -- Bit actors -- Rediscovering Charlie Chaplin -- Second thoughts on Stroheim -- Sweet and sour: Lubitsch and Wilder in old Hollywood -- Ritwik Ghatak: reinventing the cinema -- Introducing Pere Portabella -- Portabella and continuity -- Neglected filmmakers: Eduardo de Gregorio and Sara Driver -- Vietnam in fragments: William Klein in 1967-68: a radical reevaluation -- Movie heaven: defending your life -- The world as a circus: Tati's parade -- The sun also sets: the films of Nagisa Oshima --^
Inside the vault [on Spione] -- Family plot -- "The doddering relics of a lost cause": John Ford's The sun shines bright -- Prisoners of war: Bitter victory -- Art of darkness: Wichita -- Cinema of the future: still lives: the films of Pedro Costa -- A few eruptions in The House of Lava -- Unsatisfied men: Beau travail -- Viridiana on DVD -- Doing the California split -- Mise en scène as miracle in Dreyer's Ordet -- David Holzman's Diary/My girlfriend's wedding: historical artifacts of the past and present -- Early long-take climaxes -- Wrinkles in time: Alone. Life wastes Andy Hardy -- Martha: Fassbinder's uneasy testament -- India Matri Buhmi -- Radical humanism and the coexistence of film and poetry in The house is black -- WR, sex, and the art of radical juxtaposition -- Revisiting The godfather -- Film writing on the web: some personal reflections -- Goodbye, Susan, goodbye: Sontag and movies -- Daney in English: a letter to Trafic --^
Trailer for Godard's Histoire(s) du cinéma -- Moullet retrouvé (2006/2009) -- The Farber mystery -- The American cinema revisited -- Raymond Durgnat -- Surviving the Sixties -- L.A. existential.
Includes bibliographical references and index.
boek